Tindak Tutur Persuasif Guru Penjasorkes dan Siswa di SMKN 4 Bandar Lampung - Puspita Cahya Rivai; Nurlaksana Eko Rusminto; Edi Suyanto (FKIP Universitas Lampung, 2017)
The aim of this research is to describe a persuasive speech act with persuasive techniques which occurred between the physical education teacher and the students of SMKN 4 Bandar Lampung in academic year 2016/2017. This study used a descriptive qualitative method. The data sources used in this research were the speech act between the physical education teacher and the students; and also the speech act among the students of SMKN 4 Bandar Lampung which were obtained during the learning-teaching activity. The result showed that there were several persuasive speech acts with rationalization technique, suggestion technique, conformity technique, compensation technique, substitution technique, and projection technique. The persuasive speech act between the physical education teacher and the students in SMKN 4 Bandar Lampung that found the most were from the suggestion technique and the conformity technique.Tujuan penelitian ini untuk mendeskripsikan tindak tutur persuasif dengan teknik-teknik persuasi pada guru Penjasorkes dan siswa di SMK Negeri 4 Bandar Lampung tahun ajaran 2016/2017. Penelitian ini menggunakan metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah tindak tutur antara guru Penjasorkes dan siswa; serta tindak tutur antara siswa dan siswa di SMK Negeri 4 Bandar Lampung saat kegiatan pembelajaran Penjasorkes berlangsung. Hasil penelitian menunjukkan bahwa terdapat tindak tutur persuasif dengan teknik rasionalisasi, teknik sugesti, teknik konformitas, teknik kompensasi, teknik penggantian, dan teknik proyeksi. Tindak tutur persuasif pada guru Penjasorkes dan siswa di SMK Negeri 4 Bandar Lampung yang paling banyak ditemui ialah dengan teknik sugesti dan teknik konformitas.Kata kunci: persuasif, SMK Negeri 4 Bandar Lampung, tindak tutur.